2022
DOI: 10.3389/fonc.2022.920443
|View full text |Cite
|
Sign up to set email alerts
|

Improving the clinical workflow of a MR-Linac by dosimetric evaluation of synthetic CT

Abstract: Adaptive radiotherapy performed on the daily magnetic resonance imaging (MRI) is an option to improve the treatment quality. In the adapt-to-shape workflow of 1.5-T MR-Linac, the contours of structures are adjusted on the basis of patient daily MRI, and the adapted plan is recalculated on the MRI-based synthetic computed tomography (syCT) generated by bulk density assignment. Because dosimetric accuracy of this strategy is a priority and requires evaluation, this study aims to explore the usefulness of adding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Once the problem reported here was recognised, subsequent rectum cancer patients were immobilised without masks to avoid the issue, using Wing-STEP, KneeSTEP, and FeetSTEP supports (IT-V, Innsbruck, Austria) instead. A bladder catheter was used at simulation and at each treatment fraction to ensure consistent filling [ 11 , 12 ]. Simulation imaging was acquired on a Brilliance Big Bore CT (Philips Medical System, Cleveland, OH, USA) and the MR-linac’s scanner, consecutively on the same day, with the same immobilization devices.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the problem reported here was recognised, subsequent rectum cancer patients were immobilised without masks to avoid the issue, using Wing-STEP, KneeSTEP, and FeetSTEP supports (IT-V, Innsbruck, Austria) instead. A bladder catheter was used at simulation and at each treatment fraction to ensure consistent filling [ 11 , 12 ]. Simulation imaging was acquired on a Brilliance Big Bore CT (Philips Medical System, Cleveland, OH, USA) and the MR-linac’s scanner, consecutively on the same day, with the same immobilization devices.…”
Section: Methodsmentioning
confidence: 99%
“…The CT reference plan includes all the information needed to generate the sCT during the online MR-based adaptive workflow, including average EDs and a given layering priority for each contour and ppd component. The accuracy of the calculation using the sCT generated by bulk density assignment is assessed for each patient within the clinical workflow [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature has described the key benefits and adaptive radiotherapy (ART) workflows of these systems (Winkel et al 2019, de Leon et al 2022, Pham et al 2022, Rammohan et al 2022. The bulk RED override step of this workflow occurs when the voxelised CT-numbers, provided by the individual patient's simulation-CT images, are converted to an average RED value for each contoured organ (Tang et al 2022). These values are often the primary driver of dose calculation differences between tissue types and are propagated throughout the ART workflow, which includes contour adjustment or re-generation based on daily MR-images.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported on the dosimetric impact of using bulk RED overrides on MRL systems (Ding et al 2022, Green et al 2019, Pham et al 2022, Tang et al 2022. Due to the presence of the magnetic field, investigating these effects in such systems are of particular interest, especially near tissue-air boundaries which are subject to the electron return effect by the Lorentz force (Uilkema et al 2015, Green et al 2019, Pham et al 2022, Rammohan et al 2022.…”
Section: Introductionmentioning
confidence: 99%